GeoFairy: Towards a one-stop and location based Service for Geospatial Information Retrieval. (March 2017) - Sun, Ziheng; Di, Liping; Heo, Gil; Zhang, Chen; Fang, Hui; Yue, Peng; Jiang, Lili; Tan, Xicheng; Guo, Liying; Lin, Li
Abstract: It is still a great challenge to efficiently deliver dynamic and heterogeneous Earth observation (EO) information to users based on their real time locations. However, the rapidly evolving techniques create a chance to meet the challenge. This paper proposes a framework to realize a one-stop and location based service (LBS) for geospatial information (GI) retrieval on mobile platforms. The framework originally integrates a number of state-of-the-art techniques with geospatial data resources and let them cooperate together to provide a robust and highly available LBS. Cloud platform is used to deploy the server module. A location enabled load balancing algorithm is presented to balance the cloud instance VMs on behalf of LBS. A system named GeoFairy is implemented. It provides a one-stop service for gathering and delivering twelve kinds of GI on real time locations. Two Apps are built for the major mobile ecosystems: iOS and Android. Many tests, including a stress test, have been made via a number of mobile devices at various locations. The results demonstrate that GeoFairy is capable of one-stop delivering real-time GI to users and significantly reducing costs on information searching and retrieving. This feature is very helpful in many scenarios such as disaster responding and military actions. This research paves a way on both theoretical and practical aspects for researchers and developers to realize operational mobile applications for one stop and location based GI retrieval. Highlights: A One-stop LBS framework for geospatial information is invented. A mobile application called GeoFairy is implemented to deliver twelve kinds of geospatial information and validate the framework. GeoFairy paves a way for developers to realize mobile applications for one stop and location based GI retrieval